Optimizing Taste Perception to Increase Purchasing Decisions at “Warung Nenek” - Rahma, Tri Inda Fadhila; Dharma, Budi; Pane, Nurdyanti Choirunnisa; Herlin, Annisa Rahmah (Taqaddum: Community Service Journal, 2024)
The rapid growth of the culinary sector has created a highly competitive environment, compelling businesses to innovate and implement strategies to attract and retain customers. This study focuses on Rumah Makan Nenek, a popular dining spot near the State Islamic University of North Sumatra, known for its distinctive flavors and affordable prices. Despite its appeal, the restaurant faces challenges from an increasing number of dining options around the campus. Taste perception, a crucial factor in consumer purchasing decisions, plays a significant role in customer satisfaction and loyalty. This research employed Deep Interviews to gather detailed consumer feedback on taste perceptions and used Education and Training methods to enhance flavor quality and restaurant management. Additionally, Collaboration methods were applied to boost the restaurant's visibility. The findings reveal that a thorough understanding of taste perception is essential for maintaining high customer satisfaction and optimizing sales. Strategies recommended include focusing on ingredient quality, innovating recipes, conducting regular staff training, and utilizing social media for marketing. Ensuring a positive overall dining experience, including friendly service and a comfortable atmosphere, is vital for building customer loyalty and attracting new patrons. The study highlights the importance of integrating taste with other factors such as service quality and ambiance to sustain and grow in a competitive market.